Determinants of unsuccessful tuberculosis treatment outcome in Southwest Ethiopia regional state public hospitals, 2022: a multi-center case control study - Berihe Hiluf, Solomon; Abera, Abebe; Bahiru, Mesfin; Kassie, Birhanu (Frontiers in Public Health, 2024)
Background Tuberculosis is the major cause of morbidity, and it is one of the top ten causes of death globally. In Africa, the overall pooled estimate of unsuccessful tuberculosis treatment outcome was reported to be 21.1%, which is above the World Health Organization defined threshold of 15%. Unsuccessful treatment outcomes result in drug resistance, prolonged periods of infection, and increased morbidity and mortality. Therefore, this study aimed to assess determinants of unsuccessful treatment outcomes among tuberculosis patients in Southwest Ethiopia regional state public hospitals, in 2022. Method A retrospective unmatched case–control study was employed by recruiting 570 study units (190 cases and 380 controls) in three randomly selected public hospitals from 1 August 2022 to 21 August 2022. Data were collected by using a data extraction checklist adapted from tuberculosis registration logbook. Bivariate and multivariate logistic regression models were employed. A predictor variable with a p-value of less than 0.05 in the multivariate logistic regression model was taken as statistically significant. The odds ratio and 95% confidence level were used to measure the strength of the association. Result A total of 561 records (187 cases and 374 controls) were included from tuberculosis registers. In this study, the factors independently associated with unsuccessful tuberculosis treatment outcome were older age (AOR = 1.68, 95% CI: 1.142, 2.472), rural residence (AOR = 1.548, 95% CI: 1.055, 2.272), retreatment category (AOR = 2.12, 95% CI: 1.339, 3.357), underweight (BMI < 18.5 kg/m2) (AOR = 1.952, 95% CI: 1.240, 3.071), being HIV positive (AOR = 2.144, 95% CI: 1.372, 3.349) and having no treatment adherence support (AOR = 2.016, 95% CI: 1.270, 3.201). Conclusion and recommendation In this study, socio-demographic, clinical, and treatment-related factors contributed to the risk of unsuccessful treatment outcomes. Targeted interventions should be taken into consideration to diminish poor tuberculosis treatment outcomes among high-risk groups throughout the whole tuberculosis treatment course.